1995
DOI: 10.1111/j.1469-7610.1995.tb01302.x
|View full text |Cite
|
Sign up to set email alerts
|

A Twin‐Singleton Comparison of Problem Behaviour in 2‐3‐Year‐Olds

Abstract: Twin‐singleton differences in problem behaviours in 2–3‐year‐olds were studied. Maternal ratings of children's problem behaviours were obtained with the CBCL/2–3. The twin sample Consisted d 1863 twin pairs (456 MZ, 907 DZ), the sample of singletons consisted of 420 children from the general population. Results indicated that the general level of problem behaviours in twins was broadly comparable to that in singletons. Four of the seven syndromes showed lower scores for twins. These difference, however, were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(23 citation statements)
references
References 16 publications
(5 reference statements)
2
19
0
2
Order By: Relevance
“…Twins are more likely to be born premature or experience birth complications than singletons (Luke et al 1991; Spellacy et al 1990) and there is some evidence that premature birth and low birth weights are associated with precocious puberty (Ibanez et al 2000; Wehkalampi et al 2011). In general, however, studies have found that by early- to mid-childhood twins are generally representative of singletons on wide variety of physical and behavioral measures (Rutter and Redshaw 1991; Van den Oord et al 1995). Thus it is unclear to what extent twin status may affect puberty or hormone concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Twins are more likely to be born premature or experience birth complications than singletons (Luke et al 1991; Spellacy et al 1990) and there is some evidence that premature birth and low birth weights are associated with precocious puberty (Ibanez et al 2000; Wehkalampi et al 2011). In general, however, studies have found that by early- to mid-childhood twins are generally representative of singletons on wide variety of physical and behavioral measures (Rutter and Redshaw 1991; Van den Oord et al 1995). Thus it is unclear to what extent twin status may affect puberty or hormone concentration.…”
Section: Discussionmentioning
confidence: 99%
“…1995). The socioeconomic status of the parents of the twins was somewhat higher than the level in the general Dutch population (Rietveld et al.…”
Section: Methodsmentioning
confidence: 99%
“…However, assortative mating for most personality traits has been found to be low in magnitude (Maes et al, 1998). Further, twins and singletons have generally been found to experience similar rates of psychiatric disorders and behavioral and emotional problems (Gjone & Novik, 1995; Moilanen et al, 1999; Simonoff et al, 1997; van den Oord et al, 1995). There are however, two ways in which twins differ from singletons: (i) lower birth weight and shorter gestational age (Plomin et al, 2001), and (ii) delayed language development (Rutter & Redshaw, 1991).…”
Section: Potential Moderators Of Genetic and Environmental Influences On Impulsivitymentioning
confidence: 99%